DISTRIBUTION FEATURES OF WAVE CHARACTERISTICS ALONG THE COAST OF BINH THUAN PROVINCE - Mau, Le Dinh (Vietnam Journal of Marine Science and Technology, 2009)
The calculated results of significant wave height fields (H s ) along the coast of Binh  Thuan  Province  corresponding  to  typical monsoon  and  maximum  wind  fields  are presented.  Wind  data  were  taken  from  Phu  Quy  Island  Station  (1987  -  2007).  Wave characteristics  in  the  offshore  region  were  calculated  by  deep  water  wave  model  -  Dolphin. Wave characteristics in the nearshore region were calculated by SWAN model. Studied results show that Binh Thuan Coast was seriously affected by wave action in both seasons (NE and SW monsoons) with mean significant wave height of 1 to 2 m. During 1987 to 2007, the maximum winds  have  occurred  at  studied  area  with  the  velocity  of  28  m/s  and  36  m/s  in  NE  and  SW directions respectively; which generated significant wave height of 5 to 7 m and 6 to 8 m in the offshore region of studied area respectively. The headlands, nearshore islands, and shoals have an  important  role  in distribution  of  incident  wave  energy  along  Binh  Thuan  Coast.  Studied results are useful for design and construction of nearshore structures, and also, for economical, tourism, and environmental protection activities along Binh Thuan Coast.This paper is my deep sense of gratitude and respect to Prof. Vo Van Lanh (Former Director of Institute of Oceanography) who devoted the whole life for development career of oceanographic sciences in Vietnam; as well as in support and training for younger generation of  oceanographic  scientists,  the  author  is  one  among  them. He  gave  me  independence  in carrying  out research  works  and  opportunity  to  grow  in  the  challenging  subject  of oceanography, an ideal environment that any researcher could ask for.